ANALISIS SISTEM DAN PROSEDUR PEMBAYARAN PAJAK PENGHASILAN PASAL 21 PADA PEGAWAI NEGERI SIPIL (Studi pada Rumah Sakit Ngudi Waluyo Wlingi) - Mawarni, Rizqi Arum (Jurnal Mahasiswa Perpajakan, 2015)
The purpose of this study is to determine the systems and procedures for payment of income tax Article 21 and the obstacles that occur in the process of payment of Â income tax Article 21 on the Civil Service Ngudi Waluyo Hospital. The research will use qualitative method to describe how a problem that has been identified and limited the extent to which efforts to uncover the problems and circumstances as they are, so that the disclosure of the existing facts. Results of analysis in this study shows that Ngudi Waluyo Wlingi hospital is cutting system that calculation withholding tax, deposit and tax reporting is done by the treasurer. In the income tax payment procedure of Article 21 of the salaries and emoluments accounting and tax payment has been carried out properly, but the treasurer are obstacles in the process of Article 21 of the Income Tax reporting to the STO Blitar and does not make payment of income tax cut proof Article 21. Treasurer Ngudi Waluyo Hospital does report and make proof of payment of income tax cut of Article 21 because no software support for the creation of pieces of evidence and reporting to the KPP Pratama return period Blitar. Based on PMK No. 262 / PMK.03 / 2010 then treasurer of Ngudi Waluyo Wlingi Hospital should need to perform the procedure for payment of income tax article 21 as well. Key word : system and procedure, Income Tax Article 21, Civil Servants. ABSTRAK Tujuan penelitian ini adalah untuk mengetahui sistem dan prosedur pembayaran pajak penghasilan Pasal 21 serta hambatan-hambatan yang terjadi pada proses pembayaran pajak penghasilan Pasal 21 pada Pegawai Negeri Sipil di RSUD Ngudi Waluyo. Penelitian menggunakan metode kualitatif dengan analisis data menggunakan metode interaktif yaitu reduksi data, model data dan penarikan kesimpulan. Hasil analisis dalam penelitian ini menunjukan bahwa RSUD Ngudi Waluyo Wlingi menggunakan sistem pemotongan withholding tax yang penghitungan, penyetoran dan pelaporan pajaknya dilakukan oleh bendahara. Pada prosedur pembayaran PPh Pasal 21 atas gaji dan honorarium penghitungan dan penyetoran pajak sudah dilaksanakan dengan baik dan benar, tetapi bendahara terdapat hambatan dalam proses pelaporan PPh Pasal 21 tersebut kepada KPP Pratama Blitar dan tidak membuat bukti potong pembayaran PPh Pasal 21. Berdasarkan PMK Nomor 262/PMK.03/2010 maka hal tersebut sebaiknya bendahara RSUD Ngudi Waluyo perlu melakukan prosedur pembayaran PPh Pasal 21 dengan baik. Kata kunci : Sistem dan Prosedur, PPh Pasal 21 , Pegawai Negeri Sipil.